Ceramic continuous fiber with coating layer and manufacturing method thereof, ceramic matrix composite material and manufacturing method thereof
By applying a thin coating of zirconia or lanthanum oxide to ceramic fibers using impregnation and heat treatment, the method addresses the coating challenges in CMC production, achieving improved interfacial strength and damage tolerance.
Patent Information
- Application Number
- JP2021511508
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-06
- Filing Date
- 2020-03-24
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-03-24
AI Technical Summary
Existing methods for producing ceramic matrix composites (CMC) face challenges in coating the interior of fiber bundles, leading to reduced strength due to difficulty in controlling film thickness and fiber aggregation, which compromises the damage tolerance of the material.
The use of ceramic continuous fibers with a thin coating layer of metal compounds, such as zirconia or lanthanum oxide, applied through impregnation and heat treatment, prevents fiber agglomeration and enhances interfacial strength, resulting in improved damage tolerance.
The method produces CMC with enhanced interfacial strength and damage tolerance, maintaining or improving the tensile strength of the fibers while preventing adhesion between fibers and the ceramic matrix.
Smart Images

Figure 0007616048000001 
Figure 0007616048000002 
Figure 0007616048000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated ceramic continuous fiber and a method for producing the same, and a ceramic matrix composite material and a method for producing the same. [Background technology]
[0002] Ceramic matrix composites (hereafter referred to as "CMCs"), which combine ceramic continuous fibers with a ceramic matrix, are more resistant to destruction of the entire material due to the progression of scratches than ordinary ceramics (damage tolerance), and therefore are being investigated as an alternative material to heat-resistant metals such as Ni-based alloys.
[0003] Furthermore, since alumina and mullite-based oxides have high chemical stability, CMCs in which alumina and mullite-based oxides are made into continuous ceramic fibers and then composited with a ceramic matrix are expected to be used particularly as components for aircraft jet engines (e.g., Non-Patent Document 1).
[0004] The damage tolerance of CMCs is due to the selective delamination or destruction of the interface between the ceramic continuous fibers and the ceramic matrix, which suppresses the progression of damage. Therefore, if the ceramic continuous fibers and the ceramic matrix are bonded to each other, the progression of damage cannot be suppressed and the material tends to be easily destroyed.
[0005] In order to prevent adhesion between the ceramic continuous fiber and the ceramic matrix, coating the surface of the ceramic continuous fiber with a compound that promotes the destruction of the interface has been studied. However, coating by physical vapor deposition methods such as sputtering and ion plating tends to coat only the fiber surface. For this reason, chemical vapor deposition (CVD) methods and coating methods using solutions have been studied, such as a CVD method using boron nitride and a coating method using a zirconia nano-solution (ZrO2 slurry) (for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-049570 [Patent Document 2] JP 2002-173376 A [Non-patent literature]
[0007] [Non-Patent Document 1] J.AerospaceLab,Issue3,(2011)1-12. Summary of the Invention [Problem to be solved by the invention]
[0008] In general, when producing a CMC, fibers (hereinafter also referred to as "fiber bundles") in the form of an assembly of two or more fibers, such as hundreds of fibers, are used as the ceramic continuous fibers. However, in the CVD method described in Patent Document 1, it is difficult to coat the inside of the fiber bundle (it is difficult to coat the continuous fibers inside), and the strength of the obtained CMC tends to be low. In addition, in the method described in Patent Document 2, it is difficult to control the film thickness, and the continuous fibers tend to aggregate together. As a result, the strength of the obtained CMC tends to be low.
[0009] The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide a coated ceramic continuous fiber suitable for producing a ceramic matrix composite material capable of improving damage tolerance, and a ceramic matrix composite material using the same. [Means for solving the problem]
[0010] As a result of intensive research into solving the above-mentioned problems, the inventors discovered that the damage tolerance of CMCs can be improved by using a ceramic continuous fiber with a coating layer in which the coating layer and its state are controlled, and thus completed the present invention.
[0011] That is, the present invention provides coated ceramic continuous fibers shown in [1] to [4], ceramic matrix composite materials shown in [5] and [6], a method for producing coated ceramic continuous fibers shown in [7], and a method for producing a ceramic matrix composite material shown in [8].
[0012] [1] A coated ceramic continuous fiber, comprising a ceramic continuous fiber having a coating layer of a metal compound having a thickness of 50 nm or less on the surface thereof. [2] The coated ceramic continuous fiber according to [1], wherein the metal compound is at least one of a zirconium compound and a lanthanum compound. [3] The coated ceramic continuous fiber according to [1] or [2], wherein the metal compound is zirconia or lanthanum oxide. [4] The coated ceramic continuous fiber according to any one of [1] to [3], wherein the ceramic continuous fiber is at least one of an alumina continuous fiber and a mullite continuous fiber. [5] A ceramic matrix composite material comprising the coated ceramic continuous fiber according to any one of [1] to [4]. [6] The ceramic matrix composite material according to [5], having an interface strength of 10 MPa or less. [7] A method for producing a coated ceramic continuous fiber according to any one of [1] to [4], the method comprising: an impregnation step of impregnating a ceramic continuous fiber with a solution containing a metal acetylacetonate complex; and a heat treatment step of heat treating the impregnated ceramic continuous fiber. [8] A method for producing a ceramic matrix composite material, comprising a composite step of combining the coated ceramic continuous fiber according to any one of [1] to [4] with a ceramic matrix. Effect of the Invention
[0013] According to the present invention, it is possible to provide at least one of a coated ceramic continuous fiber suitable for producing a ceramic matrix composite material capable of improving damage tolerance, a ceramic matrix composite material using the same, a method for producing a coated ceramic continuous fiber, and a method for producing a ceramic matrix composite material. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1(a) is a transmission electron microscope (TEM) image of the zirconia-coated alumina continuous fiber of Example A1. FIG. 1(b) is an energy dispersive X-ray (EDS) image showing the aluminum distribution in the zirconia-coated alumina continuous fiber of FIG. 1(a). FIG. 1(c) is an EDS image showing the zirconium distribution in the zirconia-coated alumina continuous fiber of FIG. 1(a). FIG. 1(d) is an EDS image showing the oxygen distribution in the zirconia-coated alumina continuous fiber of FIG. 1(a). [Diagram 2] FIG. 2 is a graph showing the results of X-ray photoelectron spectroscopy (hereinafter also referred to as "ESCA") analysis of the surface of the zirconia-coated alumina continuous fiber of Example A1. [Diagram 3] FIG. 3(a) is a TEM image of the zirconia-coated mullite continuous fiber of Example A2. FIG. 3(b) is an EDS image showing the aluminum distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a). FIG. 3(c) is an EDS image showing the silicon distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a). FIG. 3(d) is an EDS image showing the zirconium distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a). FIG. 3(e) is an EDS image showing the oxygen distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a). [Figure 4] FIG. 4 is a graph showing the results of ESCA analysis of the surface of the zirconia-coated mullite continuous fiber of Example A2. [Diagram 5]Figure 5(a) is a TEM image of the lanthanum oxide-coated alumina continuous fiber of Example A3. Figure 5(b) is an EDS image showing the aluminum distribution in the lanthanum oxide-coated alumina continuous fiber of Figure 5(a). Figure 5(c) is an EDS image showing the lanthanum distribution in the lanthanum oxide-coated alumina continuous fiber of Figure 5(a). Figure 5(d) is an EDS image showing the oxygen distribution in the lanthanum oxide-coated alumina continuous fiber of Figure 5(a). [Figure 6] 6(a) to (c) are graphs showing the results of ESCA analysis of the surface of the lanthanum oxide-coated alumina continuous fiber of Example A3. [Figure 7] FIG. 7(a) is a TEM image of the lanthanum oxide coated mullite continuous fiber of Example A4. FIG. 7(b) is an EDS image showing the distribution of aluminum in the lanthanum oxide coated mullite continuous fiber of FIG. 7(a). FIG. 7(c) is an EDS image showing the distribution of silicon in the lanthanum oxide coated mullite continuous fiber of FIG. 7(a). FIG. 7(d) is an EDS image showing the distribution of lanthanum in the lanthanum oxide coated mullite continuous fiber of FIG. 7(a). FIG. 7(e) is an EDS image showing the distribution of oxygen in the lanthanum oxide coated mullite continuous fiber of FIG. 7(a). [Figure 8] 8(a) to (d) are graphs showing the results of ESCA analysis of the surface of the lanthanum oxide-coated mullite continuous fiber of Example A4. [Figure 9] FIG. 9 is an image of the alumina continuous fibers of Comparative Example A1 taken by a scanning electron microscope (hereinafter also referred to as "SEM"). [Figure 10] FIG. 10 is a schematic cross-sectional view showing an example of an interface strength measuring device. [Figure 11] FIG. 11 is a graph showing a stress-displacement curve in the push-out test of Measurement Example B1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, embodiments of the present invention will be described in detail, however, the present invention is not limited to the following embodiments.
[0016] [Ceramics continuous fiber with coating layer] The coated ceramic continuous fiber of one embodiment is made of a ceramic continuous fiber having a coating layer of a metal compound having a thickness of 50 nm or less on the surface. The coated ceramic continuous fiber of this embodiment can be said to have a ceramic continuous fiber and a coating layer of a metal compound having a thickness of 50 nm or less provided on the surface of the ceramic continuous fiber. In this specification, "continuous fiber" means a long fiber, particularly a thread-like long fiber that can be woven by a spinning and weaving machine. "Ceramic continuous fiber" means a continuous fiber made of ceramic. In addition, "coating layer" means a layer that covers at least a part of the continuous fiber, and "coating layer of a metal compound" means a coating layer containing a metal compound. In addition, "ceramic continuous fiber with a coating layer" means a ceramic continuous fiber having a coating layer on the surface.
[0017] In the coating layer-attached ceramic continuous fiber of this embodiment, the coating layer has a thickness of 50 nm or less. By making the coating layer thickness 50 nm or less, it is possible to prevent the ceramic continuous fibers from agglomerating together. The coating layer has a thickness of preferably 20 nm or less, more preferably 10 nm or less. There is no particular lower limit to the thickness of the coating layer, but the coating layer may have a thickness of 1 nm or more. In this embodiment, the thickness of the coating layer means a thickness measured by the distribution of the metal elements constituting the metal compound by TEM-EDS analysis. For example, when the metal compound is a zirconium compound, the thickness is measured by the distribution of zirconium, and when the metal compound is a lanthanum compound, the thickness is measured by the distribution of lanthanum.
[0018] The metal compound in the coating layer is not particularly limited as long as it is a compound containing a metal, but is preferably at least one of an oxide and a nitride containing a metal, and more preferably an oxide containing a metal. The metal compound is preferably at least one selected from the group consisting of a zirconium compound, a lanthanum compound, an yttrium compound, an iron compound, and a cerium compound, more preferably at least one of a zirconium compound, a lanthanum compound, and an yttrium compound, and even more preferably a zirconium compound or a lanthanum compound. By having a compound containing these metals as the coating layer, the ceramic continuous fiber with a coating layer becomes more suitable when used as a CMC. In another embodiment, the metal compound is preferably a compound of a metal capable of forming a metal acetylacetonate complex, and more preferably a compound of a metal capable of forming a metal acetylacetonate complex that does not react with the ceramic continuous fiber and the ceramic matrix. In this specification, the term "matrix" means a parent phase to be composited, and the term "ceramic matrix" means a matrix composed of ceramics.
[0019] From the viewpoint of heat resistance and chemical stability, the metal compound is preferably a metal oxide, and in particular, zirconia (ZrO2), lanthanum oxide (La2O3), yttrium oxide (Y2O3), iron oxide (Fe2O3), or cerium oxide (CeO2) is preferable, and the metal compound is more preferably zirconia (ZrO2), lanthanum oxide (La2O3), or yttrium oxide (Y2O3), and further preferably zirconia (ZrO2) or lanthanum oxide (La2O3).
[0020] The ceramic continuous fiber of the present embodiment is not particularly limited as long as it is a continuous fiber composed of ceramics. Examples of the ceramic continuous fiber include at least one of oxide ceramic continuous fiber and non-oxide ceramic continuous fiber. The ceramic continuous fiber is preferably at least one selected from the group consisting of silicon carbide continuous fiber, alumina continuous fiber, and mullite continuous fiber. The ceramic continuous fiber is more preferably at least one of alumina continuous fiber and mullite continuous fiber, and further preferably mullite continuous fiber. In addition, the ceramic continuous fiber preferably has a hydroxyl group on the surface.
[0021] The ceramic continuous fiber of this embodiment is preferably in the form of at least one of a fiber bundle and a woven fiber bundle, and is preferably a ceramic continuous fiber in the form of a woven fiber bundle (hereinafter also referred to as "ceramic fiber cloth").
[0022] The tensile strength of the coated ceramic continuous fiber of this embodiment measured in accordance with JIS R 1657 (hereinafter also referred to as "single fiber tensile strength") is preferably 1 GPa or more and 3 GPa or less, and more preferably 1.2 GPa or more and 2.8 GPa or less.
[0023] The coated ceramic continuous fiber of this embodiment is suitable for use as a CMC. The coated ceramic continuous fiber of this embodiment is suitable for preventing the aggregation of continuous fibers, and therefore it is possible to suppress adhesion between the coated ceramic continuous fiber and the ceramic matrix. Therefore, when it is combined with the ceramic matrix and used as a CMC, it is possible to exhibit high damage tolerance.
[0024] [Manufacturing method of coated ceramic continuous fibers] A method for producing a coating layer-attached ceramic continuous fiber according to one embodiment includes an impregnation step of impregnating a ceramic continuous fiber with a solution containing a metal acetylacetonate complex, and a heat treatment step of heat treating the impregnated ceramic continuous fiber. By impregnating the ceramic continuous fiber, chemical adsorption of the metal acetylacetonate onto the surface of the ceramic continuous fiber is promoted. The ceramic continuous fiber subjected to the impregnation step may be in the form of at least one of a fiber bundle and a ceramic fiber cloth, and is preferably a ceramic fiber cloth.
[0025] The metal acetylacetonate complex to be subjected to the impregnation step is preferably at least one of zirconium (IV) acetylacetonate (Zr(CH3COCHCOCH3)4), lanthanum (III) acetylacetonate dihydrate (La(CH3COCHCOCH3)3·2H2O), yttrium (III) acetylacetonate n-hydrate (Y(CH3COCHCOCH3)3·nH2O), iron (III) acetylacetonate (Fe(CH3COCHCOCH3)3), and cerium (III) acetylacetonate trihydrate (Ce(CH3COCHCOCH3)3·3H2O). or at least one of zirconium(IV) acetylacetonate (Zr(CH3COCHCOCH3)4), lanthanum(III) acetylacetonate dihydrate (La(CH3COCHCOCH3)3·2H2O), and yttrium(III) acetylacetonate n-hydrate (Y(CH3COCHCOCH3)3·nH2O), and more preferably at least one of zirconium(IV) acetylacetonate (Zr(CH3COCHCOCH3)4) and lanthanum(III) acetylacetonate dihydrate (La(CH3COCHCOCH3)3·2H2O).
[0026] The solvent in the solution containing the metal acetylacetonate complex is not particularly limited as long as the metal acetylacetonate complex is dissolved without being decomposed. Preferred solvents include, for example, alcohols such as methanol, ethanol, and propanol, organic solvents such as acetone and benzene, water, and heavy water. The solvent is preferably at least one of water and alcohol, and more preferably at least one of methanol and ethanol.
[0027] The impregnation may be performed under conditions that allow the chemical adsorption reaction of the metal acetylacetonate complex to proceed on the ceramic continuous fiber, and for example, the impregnation temperature may be below the boiling point of the solvent, preferably room temperature (25±3°C), and the impregnation time may be from 30 minutes to 24 hours. Since the chemical adsorption reaction is likely to be accelerated, it is preferable to perform the impregnation under heating at a temperature below the boiling point of the solvent.
[0028] The impregnation is preferably carried out so that the ratio of the area covered with the coating material to the total surface area of the ceramic continuous fiber (hereinafter also referred to as the "coverage") is 50% or more. Here, the "coating material" refers to the material used for coating. If the coverage is 50% or more, when the ceramic continuous fiber with a coating layer obtained by the manufacturing method of this embodiment is used as a CMC, adhesion between the ceramic continuous fiber with a coating layer and the ceramic matrix tends to be suppressed. The impregnation is preferably carried out so that the coverage is 75% or more, preferably 90% or more. A coverage of 100% corresponds to a state in which the coating material covers the entire surface of the ceramic continuous fiber, so the coverage is 100% or less.
[0029] The ceramic continuous fiber is preferably a ceramic continuous fiber having hydroxyl groups on the surface. In this case, the coverage can be calculated from the following formula. θ = 100 × nM × X / (S × nOH) (1) [θ is the coverage rate (%), S is the total surface area of the ceramic continuous fiber (m 2 ), nOH is the number of hydroxyl groups on the surface of the ceramic continuous fiber per unit volume (number / m 2), nM is the number of metal atoms in the metal acetylacetonate complex used in the impregnation treatment, and X is the valence of the metal atom.
[0030] When using alumina continuous fiber, the number of surface hydroxyl groups, nOH, is 12.5×10 18 (pcs / m 2 ) and when mullite continuous fiber is used, the number of surface hydroxyl groups nOH is 11.3 × 10 18 (pcs / m 2 )
[0031] The ceramic continuous fiber having hydroxyl groups on the surface is preferably at least one of an alumina continuous fiber and a mullite continuous fiber, and more preferably a mullite continuous fiber.
[0032] The method for producing the ceramic continuous fiber with a coating layer of this embodiment includes a step of heat treating the ceramic continuous fiber obtained after the impregnation step. By heat treating the ceramic continuous fiber obtained after the impregnation step, the metal acetylacetonate complex chemically adsorbed on the ceramic continuous fiber is decomposed to form a metal compound. The heat treatment conditions are not particularly limited, and the heat treatment temperature is preferably 500°C or more and 1200°C or less, more preferably 700°C or more and 1000°C or less. The heat treatment atmosphere can be appropriately selected depending on the metal compound constituting the coating layer. For example, when the metal compound is converted into an oxide, the heat treatment is performed in an oxidizing atmosphere, preferably in air, while when the metal oxide is converted into a nitride, the heat treatment is preferably performed in a nitrogen atmosphere.
[0033] In the method for producing the coated ceramic continuous fiber of the present embodiment, it is preferable to alternately repeat the impregnation step and the heat treatment step two or more times (after the first heat treatment step, the second impregnation step and the heat treatment step are performed), and it is preferable to alternately repeat the impregnation step and the heat treatment step two or more times, or five times. below Iteration is preferable.
[0034] [Ceramic matrix composites (CMC)] A ceramic matrix composite material in one embodiment has the above-mentioned coated ceramic continuous fiber, and is preferably a material in which the above-mentioned coated ceramic continuous fiber and a ceramic matrix are combined.
[0035] The ceramic matrix is at least one of an oxide ceramic and a non-oxide ceramic, preferably an oxide ceramic, more preferably at least one of alumina and mullite, and even more preferably alumina and mullite. Furthermore, it is preferable that the ceramic matrix and the ceramic continuous fibers are made of the same material.
[0036] The interfacial strength of the ceramic matrix composite material of this embodiment is preferably 10 MPa or less, more preferably 1 MPa to 10 MPa, and even more preferably 3 MPa to 8 MPa. When the interfacial strength is 10 MPa or less, the interface between the coating layer-attached ceramic continuous fiber and the ceramic matrix is more easily broken, making it difficult for the entire material to be broken, and when the interfacial strength is 1 MPa or more, the interface has a more appropriate strength.
[0037] In this embodiment, the interfacial strength can be measured by a push-out method using a cylindrical ceramic with a diameter of 2 mm and a length of 3.4 mm instead of the ceramic continuous fiber, and a CMC produced by the same method as the CMC of this embodiment using the ceramic as a measurement sample. For the push-out method, refer to Composites: Part A 32 (2001) 575-584. The tensile strength of the CMC (hereinafter also referred to as "bulk tensile strength") can be 50 MPa or more and 300 MPa or less, and preferably 50 MPa or more and 280 MPa or less. The bulk tensile strength can be measured by using a plate-shaped measurement sample with a width of 10 mm, a length of 100 mm, and a thickness of 5.0 mm, and pulling it at a load speed of 0.5 mm / min.
[0038] The content of the coated ceramic continuous fibers in the CMC is preferably 10 vol % or more and 90 vol % or less, more preferably 20 vol % or more and 70 vol % or less, based on the total volume of the ceramic matrix composite (CMC).
[0039] [Manufacturing method of ceramic matrix composites (CMC)] A method for producing a ceramic matrix composite material in one embodiment includes a compounding step of compounding the above-mentioned ceramic continuous fibers with a coating layer with a ceramic matrix.
[0040] Any method can be used for the composite formation, but a preferred method is to impregnate the ceramic continuous fibers with a slurry containing the raw materials of the ceramic matrix (hereinafter also referred to as "raw material slurry"), and then heat treat the resulting mixture. The impregnation and heat treatment steps are preferably repeated two or more times, and more preferably repeated two to five times to obtain an appropriate interfacial strength.
[0041] Since the ceramic matrix tends to become dense, it is more preferable to impregnate the raw material slurry with ceramic continuous fibers, heat treat the resulting calcined body at a temperature lower than the sintering temperature, impregnate the resulting calcined body with the raw material slurry, and sinter the impregnated calcined body.
[0042] For example, when the ceramic matrix is at least one of alumina and mullite, it is preferable to impregnate the ceramic continuous fiber with at least one of alumina and mullite raw material slurry, heat treat the resulting calcined body in air at 600°C to 1000°C, impregnate the calcined body with the raw material slurry, and then sinter the impregnated calcined body at 1050°C to 1300°C to form a composite. Prior to sintering, the impregnated calcined body may be heat treated in air at 600°C to 1000°C. In this case, the impregnation and heat treatment of the calcined body may be repeated two or more times, and preferably repeated two to five times.
[0043] The raw material slurry of at least one of alumina and mullite includes a slurry containing at least one selected from the group consisting of alumina, aluminum hydroxide, aluminum nitrate, polyaluminum chloride, and mullite. When the impregnation is performed multiple times, the composition of the raw material slurry may be different. EXAMPLES
[0044] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0045] Example A1 (Preparation of zirconia-coated alumina continuous fibers) An impregnation solution was prepared by dissolving 3.5 g of zirconium (IV) acetylacetonate (Zr(CH3COCHCOCH3)4) in 350 mL of ethanol. Alumina continuous fibers (alumina fiber cloth, 3M Japan Ltd., product name: Nextel 610) that had been desized at 700 °C in air were placed in the impregnation solution and allowed to soak at room temperature for 24 hours. The total surface area of the alumina continuous fibers was 6.2 m 2 The amount of zirconium (IV) acetylacetonate was adjusted to be in large excess relative to the coverage calculated by the above formula (1) (100% coverage: 0.0158 g), so that the coverage of the surface hydroxyl groups of the alumina continuous fiber was 100%. The alumina continuous fiber was then removed from the impregnation solution and heated at 900°C under normal pressure in the air for 2 hours. The impregnation step and heat treatment step were repeated three times to obtain a zirconia-coated alumina continuous fiber.
[0046] The surface of the obtained zirconia-coated alumina continuous fiber was photographed by TEM. FIG. 1(a) is an image of the zirconia-coated alumina continuous fiber of Example A1 photographed by TEM. FIG. 1(b) is an image showing the distribution of aluminum in the zirconia-coated alumina continuous fiber of FIG. 1(a) by EDS. FIG. 1(c) is an image showing the distribution of zirconium in the zirconia-coated alumina continuous fiber of FIG. 1(a) by EDS. FIG. 1(d) is an image showing the distribution of oxygen in the zirconia-coated alumina continuous fiber of FIG. 1(a) by EDS. As shown in FIG. 1(c), it was confirmed that a coating layer containing zirconium of 3 to 5 nm was formed on the surface of the alumina continuous fiber in the zirconia-coated alumina continuous fiber of Example A1. In addition, as shown in FIG. 1(d), oxygen was detected in the coating layer, and it was confirmed that the coating layer was composed of zirconia (ZrO2), which is an oxide. That is, it was confirmed that a zirconia coating layer having a thickness of 3 to 5 nm was formed on the surface of the alumina continuous fiber.
[0047] (ESCA analysis) Using a multi-function scanning X-ray photoelectron spectrometer (instrument name: PHI5000 VersaProbeII, manufactured by ULVAC-PHI, Inc.), ESCA analysis was performed on the zirconia-coated alumina continuous fiber in the depth direction of the alumina continuous fiber under the following conditions.
[0048] X-ray source: Monochrome Al-Kα radiation, 25W Accelerating voltage: 15kV Irradiation current: 300nA Analysis area: 100μmφ Sputtering conditions: Ion gun: Ar monomer ion (1 kV or 4 kV) Sputter depth: 0 to 200 nm (SiO2 equivalent) Sputter area: 2×2mm
[0049] Fig. 2 is a graph showing the results of ESCA analysis of the surface of the zirconia-coated alumina continuous fiber of Example A1. As shown in Fig. 2, it was confirmed that zirconium and oxygen were present near the surface (to a depth of about 15 nm) of the alumina continuous fiber.
[0050] (Measurement of single fiber tensile strength) The single fiber tensile strength of the obtained zirconia-coated alumina continuous fiber was measured in accordance with JIS R 1657. The single fiber tensile strength of the zirconia-coated alumina continuous fiber was 2.1 GPa, which was almost the same as the single fiber tensile strength (2.5 GPa) of the desized alumina continuous fiber.
[0051] Example A2 (Preparation of Zirconia-Coated Mullite Continuous Fibers) An impregnation solution was prepared by dissolving 3.5 g of zirconium (IV) acetylacetonate (Zr(CH3COCHCOCH3)4) in 350 mL of ethanol. Desized (heat-treated in air at 800°C) mullite continuous fiber (mullite fiber cloth, 3M Japan Ltd., product name: Nextel 720) was placed in the impregnation solution and allowed to soak for 24 hours at room temperature. The total surface area of the mullite continuous fiber was 5.5 m 2 The amount of zirconium (IV) acetylacetonate was adjusted to be in large excess relative to the coverage calculated by the above formula (1) (100% coverage: 0.0125 g), so that the coverage of the surface hydroxyl groups of the mullite continuous fiber was 100%. The mullite continuous fiber was then removed from the impregnation solution and heated in air at 900°C for 2 hours at normal pressure to obtain a zirconia-coated mullite continuous fiber.
[0052] The surface of the obtained zirconia-coated mullite continuous fiber was photographed by TEM. FIG. 3(a) is an image of the zirconia-coated mullite continuous fiber of Example A2 photographed by TEM. FIG. 3(b) is an image of the aluminum distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a) by EDS. FIG. 3(c) is an image of the silicon distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a) by EDS. FIG. 3(d) is an image of the zirconium distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a) by EDS. FIG. 3(e) is an image of the oxygen distribution in the zirconia-coated mullite continuous fiber of FIG. 3(a) by EDS. As shown in FIG. 3(d), it was confirmed that a coating layer containing zirconium of 3 to 7 nm was formed on the surface of the mullite continuous fiber in the zirconia-coated mullite continuous fiber of Example A2. In addition, as shown in Fig. 3(d), oxygen was detected in the coating layer, confirming that the coating layer was composed of zirconia (ZrO2), an oxide. In other words, it was confirmed that a zirconia coating layer with a thickness of 3 to 7 nm was formed on the surface of the mullite continuous fiber.
[0053] (ESCA analysis) ESCA analysis was performed on the zirconia-coated mullite continuous fiber in the depth direction of the mullite continuous fiber under the same conditions as in Example A1. Figure 4 is a graph showing the results of ESCA analysis of the surface of the zirconia-coated mullite continuous fiber of Example A2. As shown in Figure 4, it was confirmed that zirconium and oxygen were present near the surface of the mullite continuous fiber (to a depth of about 15 nm).
[0054] (Measurement of single fiber tensile strength) The single fiber tensile strength of the obtained zirconia-coated mullite continuous fiber was measured in accordance with JIS R 1657. The single fiber tensile strength of the zirconia-coated mullite continuous fiber was 1.3 GPa, which was almost the same as the single fiber tensile strength (1.5 GPa) of the desized mullite continuous fiber.
[0055] Example A3 (Preparation of lanthanum oxide coated alumina continuous fibers) Lanthanum oxide-coated alumina continuous fibers were obtained in the same manner as in Example A1, except that zirconium (IV) acetylacetonate was replaced with lanthanum (III) acetylacetonate dihydrate (La(CH3COCHCOCH3)3·2H2O). The total surface area of the alumina continuous fibers was 6.2 m. 2 The amount of lanthanum(III) acetylacetonate was adjusted to be in large excess (3.5 g) relative to the coverage calculated by the above formula (1) (100% coverage: 0.0188 g), so that the coverage of the surface hydroxyl groups of the alumina continuous fiber was 100%.
[0056] The surface of the obtained lanthanum oxide-coated alumina continuous fiber was photographed by TEM. FIG. 5(a) is an image of the lanthanum oxide-coated alumina continuous fiber of Example A3 photographed by TEM. FIG. 5(b) is an image showing the distribution of aluminum in the lanthanum oxide-coated alumina continuous fiber of FIG. 5(a) by EDS. FIG. 5(c) is an image showing the distribution of lanthanum in the lanthanum oxide-coated alumina continuous fiber of FIG. 5(a) by EDS. FIG. 5(d) is an image showing the distribution of oxygen in the lanthanum oxide-coated alumina continuous fiber of FIG. 5(a) by EDS. As shown in FIG. 5(c), it was confirmed that a coating layer containing lanthanum of 5 to 10 nm was formed on the surface of the alumina continuous fiber in the lanthanum oxide-coated alumina continuous fiber of Example A3. In addition, as shown in FIG. 5(d), oxygen was detected in the coating layer, and it was confirmed that the coating layer was composed of lanthanum oxide (La2O3), which is an oxide. That is, it was confirmed that a coating layer of lanthanum oxide having a thickness of 5 to 10 nm was formed on the surface of the alumina continuous fiber.
[0057] (ESCA analysis) ESCA analysis of the lanthanum oxide-coated alumina continuous fiber was performed under the same conditions as in Example A1. Figures 6(a) to (c) are graphs showing the results of ESCA analysis of the surface of the lanthanum oxide-coated alumina continuous fiber of Example A3. As shown in Figures 6(a) to (c), it was confirmed that lanthanum and oxygen were present in addition to aluminum derived from the fiber near the surface of the alumina continuous fiber.
[0058] (Measurement of single fiber tensile strength) The single fiber tensile strength of the obtained lanthanum oxide coated alumina continuous fiber was measured according to JIS R 1657. alumina The single fiber tensile strength of the continuous fiber was 2.7 GPa, which was almost the same as the single fiber tensile strength (2.5 GPa) of desized alumina continuous fiber.
[0059] Example A4 (Preparation of lanthanum oxide coated mullite continuous fibers) Lanthanum oxide-coated mullite continuous fibers were obtained in the same manner as in Example A2, except that zirconium (IV) acetylacetonate was replaced with lanthanum (III) acetylacetonate dihydrate (La(CH3COCHCOCH3)3·2H2O). The total surface area of the mullite continuous fibers was 5.5 m. 2 The amount of lanthanum (III) acetylacetonate was adjusted to be in large excess relative to the coverage calculated by the above formula (1) (100% coverage: 0.0149 g), and the coverage of the surface hydroxyl groups of the mullite continuous fibers was adjusted to be 100%.
[0060] The surface of the obtained lanthanum oxide-coated mullite continuous fiber was photographed by TEM. FIG. 7(a) is an image of the lanthanum oxide-coated mullite continuous fiber of Example A4 photographed by TEM. FIG. 7(b) is an image of the aluminum distribution in the lanthanum oxide-coated mullite continuous fiber of FIG. 7(a) by EDS. FIG. 7(c) is an image of the silicon distribution in the lanthanum oxide-coated mullite continuous fiber of FIG. 7(a) by EDS. FIG. 7(d) is an image of the lanthanum distribution in the lanthanum oxide-coated mullite continuous fiber of FIG. 7(a) by EDS. As shown in FIG. 7(d), it was confirmed that a coating layer containing lanthanum of 10 nm to 32 nm was formed on the surface of the mullite continuous fiber in the lanthanum oxide-coated mullite continuous fiber of Example A4. In addition, as shown in FIG. 7(e), oxygen was detected in the coating layer, and it was confirmed that the coating layer was composed of lanthanum oxide (La2O3), which is an oxide. That is, it was confirmed that a coating layer of lanthanum oxide having a thickness of about 30 nm was formed on the surface of the mullite continuous fiber.
[0061] (ESCA analysis) ESCA analysis of the lanthanum oxide-coated mullite continuous fiber was performed under the same conditions as in Example A1. Figures 8(a) to (d) are graphs showing the results of ESCA analysis of the surface of the lanthanum oxide-coated mullite continuous fiber of Example A4. As shown in Figures 8(a) to (d), it was confirmed that lanthanum and oxygen derived from lanthanum oxide were present in the vicinity of the surface of the mullite continuous fiber in addition to aluminum and silicon derived from the fiber.
[0062] (Measurement of single fiber tensile strength) The single fiber tensile strength of the obtained lanthanum oxide-coated mullite continuous fiber was measured in accordance with JIS R 1657. The single fiber tensile strength of the lanthanum oxide-coated mullite continuous fiber was 1.8 GPa, which was almost the same as the single fiber tensile strength (1.5 GPa) of the desized mullite continuous fiber.
[0063] Comparative Example A1 The alumina continuous fiber was dipped in a zirconia nano solution (solid content 30 mass%, particle size 63 nm) and then heated at normal pressure in air at 900°C for 2 hours. This process was repeated three times, and the alumina continuous fiber was observed with an SEM. The alumina continuous fiber of Comparative Example A1 has a large zirconia particle size in the zirconia nano solution, and it is expected that the thickness of the coating layer will exceed 50 nm.
[0064] Fig. 9 is an image of the alumina continuous fibers of Comparative Example A1 taken by SEM. As shown in Fig. 9, it was confirmed that the alumina continuous fibers of Comparative Example A1 were aggregated together by zirconia particles.
[0065] Example B1 (Fabrication of Ceramic Matrix Composites (CMC)) A raw powder was prepared by mixing 25% by mass of roughly spherical α-alumina powder with an average particle size of 0.19 μm and 75% by mass of mullite powder with an average particle size of 1.66 μm. 350 g of the raw powder was mixed with 146 g of pure water in a ball mill to obtain a mixed slurry of alumina and mullite.
[0066] Next, the zirconia-coated alumina continuous fiber obtained in Example A1 was impregnated with a mixed slurry of alumina and mullite, and then dried at a temperature of 70°C and a relative humidity of 95% to obtain a molded body having a width of 110 mm, a length of 110 mm, and a thickness of about 5.0 mm. The molded body was dried overnight at 120°C in the air, and then heat-treated at 900°C in the air for 2 hours to obtain a calcined body.
[0067] The calcined body was dissolved in about 10% by mass of polyaluminum chloride aqueous solution ([Al(OH) n Cl 6-n ] m The calcined body was sintered in air at 1100°C for 2 hours to obtain a sintered body, a plate-shaped CMC. The obtained plate-shaped CMC contained 33.4% by volume of fibers and had a density of 2.48 g / cm.3 The density of the CMC was measured by the Archimedes method.
[0068] (Measurement of bulk tensile strength) The obtained CMC was processed to a width of 10 mm, length of 100 mm, and thickness of 5.0 mm, and aluminum tabs were attached to both ends to prepare a tensile test specimen. The width and thickness of the tensile test specimen were measured using a micrometer, and the length of the test specimen was measured using a vernier caliper. A tensile strength test was performed at a load rate of 0.5 mm / min using a strength tester (manufactured by Shimadzu Corporation, device name: AG-XPlus) and a tensile test jig. The number of test specimens for the tensile strength test was 5, and the average value of the 5 specimens was taken as the bulk tensile strength. The bulk tensile strength of the obtained CMC was 80 MPa.
[0069] (Interface strength measurement) The interfacial strength of the obtained CMC was measured by a push-out test in which an alumina rod with a surface coating of a metal acetylacetonate complex was prepared in the same manner as in the production of the coated ceramic continuous fiber, and only the alumina rod was pressed into the rod using a strength testing machine (manufactured by Shimadzu Corporation, device name: AG-2000B) to measure the interfacial strength of the obtained CMC.
[0070] Fig. 10 is a schematic cross-sectional view showing an example of an interface strength measuring device. The interface strength measuring device 10 shown in Fig. 10 mainly comprises an evaluation sample 5 consisting of a surface-coated alumina rod 3 and a ceramic matrix 4, a strength tester 1 for pressing the surface-coated alumina rod 3 in a direction A, an indenter 2 connected to the strength tester 1 and pressing the surface-coated alumina rod 3, and a fixing table 6 for fixing the ceramic matrix 4 portion of the evaluation sample 5.
[0071] The interfacial strength was measured by first preparing a cylindrical alumina rod (diameter 2 mm × length 3.4 mm) and coating the surface of the alumina rod (diameter 2 mm × length 3.4 mm) with the metal acetylacetonate complex used in the preparation of the ceramic continuous fiber with coating layer to prepare a surface-coated alumina rod 3. Next, the raw material powder used in the preparation of the CMC was prepared, and the surface-coated alumina rod 3 was embedded in the raw material powder and molded by die pressing and cold isostatic pressing at a pressure of 200 MPa to prepare a molded body (diameter 21 mm × length 3.4 mm) in which the surface-coated alumina rod 3 was embedded. The molded body was then treated in the same manner as in the preparation of the CMC to obtain an evaluation sample 5 consisting of the surface-coated alumina rod 3 and the ceramic matrix 4. Only the ceramic matrix 4 portion of the evaluation sample 5 was fixed to a fixing table 6, and the surface-coated alumina rod 3 portion was pressed using a stainless steel indenter 2 with a diameter of 1 mm, and the stress-strain curve at this time was obtained. The interface strength τ is calculated from the maximum load P in the stress-strain curve and the contact area between the surface-coated alumina rod 3 and the ceramic matrix 4 according to formula (2). τ=Pmax / (2πrl) (2) [In formula (2), Pmax is the maximum load in the stress-displacement curve in the push-out test, π is the circumference ratio, r is the radius of the alumina rod, and l is the length of the alumina rod.]
[0072] In other words, in this interfacial strength measurement, in an evaluation sample in which a surface-coated alumina rod and a ceramic matrix are composited, the interfacial strength between the surface-coated alumina and the ceramic matrix can be measured by pressing the surface-coated alumina rod into the sample, and the interfacial strength of the CMC can be measured.
[0073] Measurement example B1 (interface strength measurement) A mixed slurry of alumina and mullite was prepared in the same manner as in Example B1, and dried to obtain a raw material powder. Next, 0.5 g of zirconium (IV) acetylacetonate (Zr(CH3COCHCOCH3)4) was dissolved in 50 mL of ethanol to obtain a powder with a total surface area of 0.094 m 2The alumina rod was impregnated at room temperature for 24 hours. At this time, the amount added was made to be in large excess of the amount required for the coverage rate calculated by the above formula (1) to be 100%. Here, the coverage rate of the alumina rod was calculated by the above formula (1) in the same manner as for the ceramic continuous fiber (the alumina rod is a ceramic having a hydroxyl group on the surface and is coated with a metal acetylacetonate complex (zirconium (IV) acetylacetonate), so the coverage rate can be calculated by the above formula (1)). Thereafter, the alumina rod was taken out and heat-treated in air at 900°C for 2 hours. The impregnation process and heat treatment process (hereinafter also referred to as "surface coating treatment") were repeated three times to obtain a zirconia-coated alumina rod.
[0074] Next, the zirconia-coated alumina rod was embedded in the raw material powder and molded by a die press, and then processed by a cold isostatic press at a pressure of 200 MPa to obtain a molded body in which the zirconia-coated alumina rod was embedded in the center of a cylinder with a diameter of 20 mm and a thickness of 4 mm. The obtained molded body was sintered in air at 900 ° C for 2 hours to obtain a calcined body. The obtained calcined body was impregnated with a polyaluminum chloride aqueous solution and heat-treated three times in the same manner as in Example B1, and then sintered in air at 1100 ° C for 2 hours in the same manner as in Example B1 to produce a sintered body in which the alumina rod and the ceramic matrix were sintered together.
[0075] The obtained sintered body was ground with sandpaper so that the zirconia-coated alumina rods protruded from both sides of the cylinder, to obtain a test piece (evaluation sample) with a diameter of 21 mm and a thickness of 3.4 mm. The interface strength in the push-out test was 9.8 MPa. Figure 11 is a graph showing the stress-displacement curve in the push-out test of Measurement Example B1. The arrow in Figure 11 indicates the maximum load (Pmax).
[0076] ·Measurement example B2 (interface strength measurement) A push-out test piece (evaluation sample) was obtained in the same manner as in Measurement Example B1, except that the surface coating treatment of the alumina rod was performed only once. The interface strength in the push-out test was 7.3 MPa. This measurement example shows that the interface strength is improved by repeating the surface coating treatment.
[0077] Measurement example B3 (interface strength measurement) 0.00012 g of zirconium(IV) acetylacetonate (Zr(CH3COCHCOCH3)4) was dissolved in 50 mL of ethanol to obtain a solution with a total surface area of 0.094 m 2 The alumina rod was impregnated at room temperature for 24 hours. At this time, the coverage calculated by formula (1) was 50%. A push-out test piece (evaluation sample) was obtained in the same manner as in Measurement Example B1, except that the zirconia-coated alumina rod thus prepared was used. The interface strength in the push-out test was 7.6 MPa. This measurement example shows that the interface strength is improved by increasing the coverage.
[0078] ·Measurement example B4 (interface strength measurement) 0.5 g of lanthanum acetylacetonate dihydrate (La(CH3COCHCOCH3)3·2H2O) was dissolved in 50 mL of ethanol to obtain a total surface area of 0.094 m 2 The alumina rod was impregnated at room temperature for 24 hours. At this time, the amount added was made to be in large excess of the amount required to obtain a coverage of 100% as calculated by the above formula (1). A push-out test piece (evaluation sample) was obtained in the same manner as in Measurement Example B1, except that the coated alumina rod thus prepared was used. The interface strength in the push-out test was 7.0 MPa.
[0079] Example B2 (Fabrication of Ceramic Matrix Composites (CMC)) 350 g of roughly spherical α-alumina powder having an average particle size of 0.19 μm and 146 g of pure water were mixed in a ball mill to obtain an alumina slurry.
[0080] Next, Examples A4The lanthanum oxide-coated mullite continuous fibers obtained in step 1 were impregnated in an alumina mixed slurry and dried to obtain a molded body with a width of 110 mm, length of 110 mm, and thickness of approximately 0.5 mm. The molded body was dried overnight at 120°C in air, and then heat-treated at 1100°C for 2 hours in air to obtain CMC.
[0081] (Measurement of bulk tensile strength) The obtained CMC was processed to a width of 10 mm, length of 100 mm, and thickness of 0.5 mm, and aluminum tabs were attached to both ends to prepare a tensile test specimen. The width and thickness of the tensile test specimen were measured using a micrometer, and the length of the test specimen was measured using a vernier caliper. A tensile strength test was performed at a load rate of 0.5 mm / min using a strength tester (manufactured by Shimadzu Corporation, device name: AG-XPlus) and a tensile test jig. The number of test specimens for the tensile strength test was four, and the average value of the four specimens was taken as the bulk tensile strength. The bulk tensile strength of the obtained CMC was 141 MPa.
[0082] Comparative Example B1 A CMC was obtained in the same manner as in Example B1, except that alumina continuous fibers (alumina fiber cloth, manufactured by 3M Japan Ltd., product name: Nextel 610) that had been desized (heat-treated in air at 700°C) were used instead of the zirconia-coated alumina continuous fibers (i.e., alumina continuous fibers that were not zirconia-coated were used). The fiber volume fraction of the CMC was 34.1% by volume, and the density of the CMC was 2.35 g / cm. 3 The bulk tensile strength was 9 MPa, which was lower than that of the CMC of Example B1.
[0083] ·Comparative measurement example B1 (interface strength measurement) A push-out test piece was obtained in the same manner as in Example B1, except that an alumina rod without surface coating was used. The interface strength in the push-out test was 13.6 MPa. From this example, it is considered that the fracture occurred due to adhesion between the ceramic continuous fiber and the ceramic matrix in the CMC of Comparative Example B1.
[0084] Comparative example B2 A CMC was obtained in the same manner as in Example B2, except that a desized (heat-treated at 700°C in air) mullite continuous fiber (mullite fiber cloth, manufactured by 3M Japan Ltd., product name: Nextel 720) was used instead of the lanthanum oxide-coated mullite continuous fiber (i.e., a mullite continuous fiber not coated with lanthanum oxide was used). The bulk tensile strength was 107 MPa, which was lower than that of the CMC in Example B2.
[0085] From the above, it was found that the CMC of Example B1 having a ceramic continuous fiber with a coating layer was superior in strength to the CMC of Comparative Example B1 having a ceramic continuous fiber without a coating layer on its surface, as compared with Measurement Example B1 and Comparative Measurement Example B1. Also, it was found that the CMC of Example B1 was superior in strength to the CMC of Example B2 having a ceramic continuous fiber with a coating layer and the CMC of Comparative Example B2 having a ceramic continuous fiber without a coating layer on its surface. From these results, it was confirmed that the ceramic continuous fiber with a coating layer of the present invention is suitable for producing a ceramic matrix composite material having sufficiently high strength. [Industrial Applicability]
[0086] The coated ceramic continuous fiber of the present invention can be used as a CMC with high damage tolerance such as tensile strength, because there is almost no aggregation of metal compounds in the surface coating of the ceramic continuous fiber. In addition, the coated ceramic continuous fiber of the present invention can be produced by impregnating the ceramic continuous fiber with a solvent containing a metal acetylacetonate complex, so that coating treatment can be easily performed not only on two-dimensional cloth-shaped woven fabrics, but also on woven fabrics or nonwoven fabrics with complex three-dimensional shapes, enabling wide industrial use. [Explanation of symbols]
[0087] 1...strength tester, 2...indenter, 3...surface-coated alumina rod, 4...ceramic matrix, 5...evaluation sample, 6...fixing table, 10...interface strength measuring device.
Claims
1. A method for producing a ceramic continuous fiber, comprising: an impregnation step of impregnating a ceramic continuous fiber with a solution containing a metal acetylacetonate complex; and a heat treatment step of heat treating the impregnated ceramic continuous fiber. A method for producing a coated ceramic continuous fiber, comprising the steps of: forming a coating layer of a metal compound having a thickness of 50 nm or less on the surface of the ceramic continuous fiber;
2. The method for producing a coated ceramic continuous fiber as described in claim 1, wherein the metal acetylacetonate complex is one or more selected from the group consisting of zirconium (IV) acetylacetonate, lanthanum (III) acetylacetonate dihydrate, yttrium (III) acetylacetonate n-hydrate, iron (III) acetylacetonate, and cerium (III) acetylacetonate trihydrate.
3. A manufacturing method described in claim 1 or 2, wherein the ceramic continuous fibers are at least one of alumina continuous fibers and mullite continuous fibers.
4. A manufacturing method described in any one of claims 1 to 3, wherein the heat treatment temperature in the heat treatment step is 500°C or higher and 1200°C or lower.
Citation Information
Patent Citations
Coating inorganic fiber toughened MAX phase ceramic composite material, preparation method and uses thereof
CN103910532A
Fiber coating by atomic layer deposition
GB2467928A
Surface treatment of carbon fiber
JP1989127633A
Ceramic / fiber composite material and preparation thereof
JP1990188471A
Coated reinforcing fiber and method for forming oxide barrier coating
JP1991185179A